Agricultura y desarrollo. Las instituciones de cooperación y ayudahacia América Latina y el Caribe - Prato Barbosa, Nelson (The International Journal of Sociology of Agriculture and Food, 1991)
The main objective of this paper is to expose a research project to analyze the historic variations of knowledge and information about Latin America and the Caribbean among public and private institutions, which offer aid and cooperation to that region in the agricultural field. Our aim is to determine how the historic image of Latin America and the Caribbean has affected the criteria of those institutions in their perception of the Region's problems and their solutions, and related cooperation policies and international aid. Likewise, the project will make a diagnosis of the economic, financial, scientific and technological aid offered by the Developed Countries and Multinational Programs for Development (FAO, PNUD, etc.) to Latin America and the Caribbean agriculture. The research intends, a posteriori, to compare the present levels of institutional development for cooperation and aid to Latin America and the Caribbean in agricultural fields, among the countries and regions selected for the study. This will help in the plans for more solidarity and egalitarian cooperation mechanisms, based on mutual knowledge and respect for the cultural, political and social ethos which historically determine their identities.?Agricultura y desarrollo. Las instituciones de cooperación y ayudahacia América Latina y el Caribe                           Resumen           ?El objetivo central del proyecto es tratar de conocer las tendencias históricas de los programas de cooperación y ayuda hacia América Latina y el Caribe que tienen las instituciones gubernamentales y privadas de los países desarrollados, así como de las agencias multinacionales. Se trata de establecer el modo cómo la imagen que históricamente se ha tenido sobre América Latina y el Caribe, ha afectado los criterios que utilizan dichas instituciones para evaluar los problemas y salidas hacia el futuro de la Región, así como, en la formulación de sus políticas de cooperación y asistencia internacional.El Proyecto de Investigación pretende, a posteriori, hacer comparaciones sobre los tipos y carácter de las instituciones existente en los países altamente industrializados y organismos internacionales para el desarrollo (FAO, PNUD, etc) para la cooperación y asistencia a los países de América Latina y el Caribe en diferentes ámbitos de la agricultura.